Manajemen Pendidikan Pada Tadris Bahasa Indonesia STAIN Curup - Murniyanto, Murniyanto; Khair, Ummul (Tadbir : Jurnal Studi Manajemen Pendidikan, 2019)
This study aims to describe how education management in the Indonesian language structure STAIN Curup. This type of research is field research with a qualitative descriptive approach, the subjects of this study are the department heads, lecturers, study program staff and students. Data collection techniques through interviews, observation and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. Data manipulation and techniques.The results of this study indicate that: 1) leadership in the management of education in the Indonesian STAIN Curup tadris has been well implemented, 2) efforts to improve the management aspects of education in the Indonesian language system at STAIN Curup have been implemented is the autonomy of study programs in improving education quality. as an effort to seek input and increase enthusiasm to make a positive contribution to the study program. Transparency of one of the principles of good governance or good governance of the organization is needed to build a successful organization. Teamwork collaboration is needed because cooperation will provide better work results, but cooperation is still low. Management of education in the Indonesian language class has had a positive impact on study programs.